(untitled) (Zoological Records and Reviews, 2024)
Road networks are one of the most pervasive anthropogenic stressors on terrestrial wildlife, generating direct mortality through vehicle collisions, indirect mortality through barrier effects on movement and dispersal, and sub-lethal stress responses that reduce fitness in adjacent populations. This study provides a comprehensive assessment of wildlife road mortality across Spain, Sweden, and Germany using systematic carcass monitoring on 2,840 km of surveyed road transects (2021-2023), national road casualty databases, and GPS telemetry data for six focal mammal and herpetofaunal species (n = 184 tagged individuals). A total of 48,241 vertebrate road casualties were recorded across 312 taxonomic categories, yielding an estimated national mortality of 4.8-8.4 million vertebrates annually in Spain, 2.1-3.6 million in Sweden, and 6.2-10.8 million in Germany. Road type and traffic volume were the strongest predictors of casualty rate (GLMM: beta = 0.72 and 0.64 respectively; p < 0.001 both), while proximity to woodland edge (< 200 m) doubled mammal collision risk. GPS telemetry confirmed that road-crossing attempts constituted 18.4-34.7% of mortality events in telemetered individuals of Capreolus capreolus and Bufo bufo. Hotspot analysis using kernel density estimation identified 847 priority road segments (< 1% of monitored road length) accounting for 34.8% of all casualties. Cost-benefit analysis of mitigation measures – wildlife passages, drift fences, exclusion fencing, and speed reduction – shows that passage infrastructure at hotspot locations achieves a benefit-cost ratio of 3.4-8.1 depending on species composition and traffic volume. These findings provide an evidence base for prioritising road ecology mitigation under EU Green Infrastructure Strategy and TEN-T network management obligations.